2015
DOI: 10.18052/www.scipress.com/ilcpa.52.28
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Dexlansoprazole in Bulk and Spiked Human Plasma by Extraction Spectrophotometry

Abstract: ABSTRACT. This paper describes a simple extraction spectrophotometric method for the quantification of dexlansoprazole in bulk and spiked human plasma. This method involves formation of stable yellow colored chloroform extractable ion-pair complex of the amino derivative of dexlansoprazole with acid dye, namely methyl orange in acidic medium. The ion-pair complexes exhibit absorption maxima at 425 nm. Dexlansoprazole can be determined up to 4-40 μg/mL by the proposed method. The effect of optimum reagent conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A through literature search has revealed that only few spectrophotometric methods available for determination of DXL in pure and dosage forms. 10,11 However, many of the above methods suffered from one or other disadvantage like poor sensitivity, require high cost solvents in addition to elaborate treatment, need tedious extraction procedures, measurements done at shorter wavelengths, heating or cooling step, use of expensive chemical and/or complicated experimental set-up. Spectrophotometric technique, because of simplicity and low cost, sensitivity and selectivity, significant accuracy and precision and broad availability and applicability for pharmaceutical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A through literature search has revealed that only few spectrophotometric methods available for determination of DXL in pure and dosage forms. 10,11 However, many of the above methods suffered from one or other disadvantage like poor sensitivity, require high cost solvents in addition to elaborate treatment, need tedious extraction procedures, measurements done at shorter wavelengths, heating or cooling step, use of expensive chemical and/or complicated experimental set-up. Spectrophotometric technique, because of simplicity and low cost, sensitivity and selectivity, significant accuracy and precision and broad availability and applicability for pharmaceutical analysis.…”
Section: Introductionmentioning
confidence: 99%